2011
DOI: 10.1097/mrr.0b013e32833d6cb2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of papaverine and sildenafil in the treatment of erectile dysfunction in early-stage paraplegic men

Abstract: The aim of the study was to determine which vasoactive agent was more efficacious for erectile dysfunction (ED), intracavernosal papaverine or oral sildenafil, in paraplegic men within the first year after injury by using a penile color Doppler ultrasound as a quantitative imaging method and to determine the association between responses to these two vasoactive agents and factors such as neurological lesion level and lesion severity. A total of 31 male in-patients with spinal cord injury, aged over 18 years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Papaverine is an ergot alkaloid first isolated in 1848 (16) from Papaver somniferum. Papaverine does not have narcotic properties, but was used as a smooth muscle relaxant for the treatment of vasospasm and erectile dysfunction (17,18). Its vascular effects were thought to be due to its activity as a phosphodiesterase 10A inhibitor (19).…”
Section: Papaverine and Its Derivatives Radiosensitize Solid Tumors Bmentioning
confidence: 99%
“…Papaverine is an ergot alkaloid first isolated in 1848 (16) from Papaver somniferum. Papaverine does not have narcotic properties, but was used as a smooth muscle relaxant for the treatment of vasospasm and erectile dysfunction (17,18). Its vascular effects were thought to be due to its activity as a phosphodiesterase 10A inhibitor (19).…”
Section: Papaverine and Its Derivatives Radiosensitize Solid Tumors Bmentioning
confidence: 99%
“…Papaverine, a non-narcotic opium alkaloid, is isolated from Papaver somniferum [8]. Medicinal papaverine is used as a smooth muscle relaxant for the treatment of vasospasm and erectile dysfunction and functions by inhibiting phosphodiesterase 10A [911]. In cancer research, papaverine showed selective anticancer effects in several tumor cells, including prostate carcinoma LNCaP [12, 13] and PC-3 [14]; colorectal carcinoma HT29 [15]; breast carcinoma T47D [15], MCF-7, and MDA-MB-231 [16]; fibrosarcoma HT1080 [15]; and hepatocarcinoma HepG2 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical studies were excluded because a single dose of sildenafil 50 mg was used once to see the effect on ED, and the other simply to determine the side effects of the drug on SCI patients with ED [21,22]. Regarding the reliability of the studies, one article was excluded because the authors did not report the dosage of sildenafil used for treating individuals with SCI and ED, and there was a possible bias based on the fact that 10 out of the 16 were concomitantly treating their ED with intracavernous alprostadil injection [23].…”
Section: Resultsmentioning
confidence: 99%